Walki powstańcze o Rawę w 1863 roku - Puś, Wiesław (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2013)
The city of Rawa was taken over by insurgents three times during the uprising of 1863. For the time Rawa was conquered on 4 February 1863, by a squad of the Colonel Antoni Jeziorański. Capture of the city took place after a bloody battle with a russian squad that stationed in Rawa. The barracks filled with hundreds of russian soldiers were attacked by troop of 600 polish insurgents around midnight. As the result of setting wooden barracks on fire the battle ended with the defeat of the Russians. However after a few hours after the capturing of Rawa the insurgents left the city in fear of coming Russian troops. After that the city of Rawa has been seized by insurgents twice: on February 9th 1863 the troop of Józef Leniecki captured the city for a few hours. The same year, during the night of May 17th / 18th Kajetan Słupski’s squad invade the Rawa for a few hours and then left the city.